Non-woven Fabrics - Jeon, Han-Yong (IntechOpen, 2016)
Non-woven Fabrics is differentiated text which covers overall stream from raw fibers to final products and includes features of manufacturing and finish process with specialized application end use. Application range of non-woven fabrics is extended to all the industrial fields needless to say apparel, such as ICT (information and communication technology), bio- and medicals, automobiles, architectures, construction and environmental. Every chapter is related to the important and convergent fields with the technical application purpose from downstream to upstream fields. Also, applicability of non-woven fabrics is introduced to be based on the structural analysis of dimensional concept and various non-woven fabrics as a state-of-art embedded convergent material are emphasized in all industry fields by using nanofibers and carbon fibers.